(untitled) (Research Nepal Journal of Development Studies, 2023)
A review on opportunities and challenges of Buddhists Education is a study to review the Buddhist education. It is difficult to review the challenges and opportunities of overall Buddhist education; however, the review has started its research. It is a qualitative library research based on available resources. Thus it has not tested any hypothesis and visited filed to collect data. In conclusion, there are many opportunities and challenges in Buddhist education in postmodern world. Thus everyone has to grab the opportunities and minimize the challenges as mention in the study.